(untitled) (Torani Journal of Fisheries and Marine Science, 2019)
Aquatic plants are an indicator of the fertility of an aquatic region. The waters of Lake Tempe are the largest waters of the lake area in South Sulawesi. Lake Tempe is located in the western part of Wajo District, precisely in Tempe District, about 7 km from Sengkang City towards the banks of the Walanae River in southern Sulawesi. The area is about 13,000 ha with a maximum depth of 5.5 m and can reach more than 30,000 ha during floods, and during the dry season, the inundation area reaches only 1,000 ha with a maximum depth of 1 m, located above the continental and Australian and Asian plates. This lake is one of the tectonic lakes in Indonesia. Every year silting the lake occurs. The Tempe hydro vegetation and eco-physical research were carried out in October 2017. The purpose of this study was to record aquatic plant species that live in Tempe Lake and observe ecological changes and physical properties of Lake Tempe. Aquatic plants are expected to be able to filter lake water. The results obtained are physical conditions of sharp-smelling water, unpleasant taste, dark brown, and cloudy color. Chemical indicators of NH3-N waters (0.2976-0.0634), PO4-P (0.0172-0.0844) NO2-N (undetectable), NO3-N (1.7131-1.9335), Sulphate (27.761900 - 37.047620), DO (6.88-7.18) and pH (7.88-8.02). There are 14 species of aquatic plants found in these waters. The most dominant species is water hyacinth. In the case of Tempe lake water vegetation results in siltation of the lake area. Keywords: Aquatic plant, Biodiversity, Species, Tempe lake,